Nonlinear and shock waves in superfluid He II - Kolmakov, G.V.; Efimov, V.B.; Ganshin, A.N.; McClintock, P.V.E.; Lebedeva, E.V.; Mezhov-Deglin, L.P. (Физика низких температур, 2006)
We review studies of the generation and propagation of nonlinear and shock sound waves in
He II (the superfluid phase of ⁴He), both under the saturated vapor pressure (SVP) and at elevated
pressures. The evolution in shape of second and first sound waves excited by a pulsed heater
has been investigated for increasing power W of the heat pulse. It has been found that, by increasing
the pressure P from SVP up to 25 atm, the temperature Tα, at which the nonlinearity coefficient
of second sound reverse its sign, is decreased from 1.88 to 1.58 K. Thus at all pressures
there exists a wide temperature range below Tλ where α is negative, so that the temperature discontinuity
(shock front) should be formed at the center of a propagating bipolar pulse of second
sound. Numerical estimates show that, with rising pressure, the amplitude ratio of linear first and
second sound waves generated by the heater at small W should increase significantly. This effect
has allowed us to observe at P 133. atm a linear wave of heating (rarefaction) in first sound, and
its transformation to a shock wave of cooling (compression). Measurements made at high W for
pressures above and below the critical pressure in He II, Pcr 22. atm, suggest that the main reason
for initiation of the first sound compression wave is strong thermal expansion of a layer of He I
(the normal phase) created at the heater-He II interface when W exceeds a critical value. Experiments
with nonlinear second sound waves in a high-quality resonator show that, when the driving
amplitude of the second sound is sufficiently high, multiple harmonics of second sound waves are
generated over a wide range of frequencies due to nonlinearity. At sufficiently high frequencies the
nonlinear transfer of the wave energy to sequentially higher wave numbers is terminated by the
viscous damping of the waves.